Alternative language paradigms for functional magnetic resonance imaging as presurgical tools for inducing crossed cerebro-cerebellar language activations in brain tumor patients. - Thakkar, Ishani; Arraño-Carrasco, Leonardo; Cortes-Rivera, Barbara; Zunino-Pesce, Romina; Mery-Muñoz, Francisco; Rodriguez-Fernández, María; Smits, Marion; Mendez-Orellana, Carolina (European Radiology, 2022)
Objectives: Crossed cerebro-cerebellar BOLD activations have recently come to light as additional diagnostic features for patients with brain tumors. The covert verb generation (VG) task is a widely used language paradigm to determine these language-related crossed activations. Here we demonstrate these crossed activations in two additional language paradigms, the semantic and phonological association tasks. We propose the merit of these tasks to language lateralization determination in the clinic as they are easy to monitor and suitable for patients with aphasia.Methods: Patients with brain tumors localized at different cortical sites (n = 71) performed three language paradigms, namely the VG task as well as the semantic (SA) and phonological (PA) association tasks with button-press responses. Respective language activations in disparate cortical regions and the cerebellum were assigned laterality. Agreements in laterality between the two new tasks and the verb generation task were tested using Cohen's kappa.Results: Both tasks significantly agreed in cortical and cerebellar lateralization with the verb generation task in patients. Additionally, a McNemar test confirmed the presence of crossed activations in the cortex and the cerebellum in the entire subject population.Conclusion: We demonstrated that the semantic and phonological association tasks resulted in crossed cerebro-cerebellar language lateralization activations as those observed due to the covert verb generation task. This may suggest the possibility of these tasks being used conjointly with the traditional verb generation task, especially for subjects that may be unable to perform the latter.Key Points: • The semantic and phonological association tasks can be useful as additional presurgical fMRI language lateralization paradigms for brain tumor patients along with the standard verb generation task. • All three tasks also confirm the presence of crossed cerebro-cerebellar language activations in the current subject population.